Symposium 4: Learning from peers: Online professional development for university staff - Macdonald, Janet; Campbell, Anne (Proceedings of the International Conference on Networked Learning, 2010)
Professional development has long been associated with the provision of events or alternatively of accredited courses, often supplemented by texts or websites. At the same time we are aware that much of what is learnt about university teaching happens “on the job”, as staff try out new approaches, or meet each other for a chat in the corridor. In a distance environment such ad hoc arrangements are less likely to take place particularly for part-time staff, and both online courses and informal communities have a particular role in joining staff who otherwise have little opportunity to meet. We have been exploring the opportunities for harnessing the potential of peer learning in two online professional development courses at the Open University (UK) both of which are concerned with the adoption of new online tools for teaching and learning. This paper describes a case study of the two initiatives which deliver professional development at scale: some 2000 staff have undertaken the courses to date, including an astonishing 1000 staff over the last 12 months. We discuss some of the lessons we have learnt on the reasons for the widespread success of these initiatives and some of the factors influencing effective engagement on the courses. We have demonstrated the value of a near-synchronous strategy in a small cohort which enhances a sense of presence, while providing sufficient flexibility to accommodate working practices. An experiential approach which gives participants the opportunity to experience first hand the sense of being an online student is valued by many staff who are new to it, and it provides a safe environment in which to try out new techniques and tools and to reflect on what is a pressing concern for many staff. The affective, confidence building aspects of this experience seem to have been important to many participants. At the same time we have also found that a self study route can work for some individuals who value the added flexibility to work on their own. Further work will be needed to establish the extent to which the courses have resulted in new or enhanced working practices. But if we have succeeded in helping staff to develop the confidence to experiment for themselves, then this will have been a worthwhile endeavour.